Evaluating Interreligious Peacebuilding and Dialogue Methods and Frameworks - Abu-Nimer, Mohammed; Katalin Nelson, Renáta (KAICIID - Beyond Dialogue Series, 2021)
Featuring chapters by well-established interreligious peacebuilders from around the world, this volume examines the challenges and implications faced by religious and interreligious peacebuilders and provides new models and tools for monitoring and evaluating religious and interreligious peacebuilding projects. It is a critical tool and point of reference for those developing and implementing religious and interreligious peacebuilding projects.